2016
DOI: 10.2967/jnumed.116.176552
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Image Reconstruction for 90Y Selective Internal Radiotherapy on a Lutetium Yttrium Orthosilicate PET/CT System Using a Bayesian Penalized Likelihood Reconstruction Algorithm

Abstract: Imaging on a γ-camera with Y after selective internal radiotherapy (SIRT) may allow for verification of treatment delivery but suffers relatively poor spatial resolution and imprecise dosimetry calculation.Y PET/CT imaging is possible on 3-dimensional, time-of-flight machines; however, images are usually poor because of low count statistics and noise. A new PET reconstruction software using a Bayesian penalized likelihood (BPL) reconstruction algorithm (termed Q.Clear) was investigated using phantom and patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 18 publications
3
39
0
Order By: Relevance
“…Results also open the question of the Q.Clear reconstruction optimization for each different radiopharmaceutical and clinical application. For example, it was recently reported that for 90 Y TOF PET imaging a β value of 4000 is the recommended choice, far more elevated than the values considered in the present work. This extreme case is due to the low statistics of 90 Y PET imaging, so different results than those presented in this study can be achieved for other nuclides or pharmaceuticals.…”
Section: Discussionmentioning
confidence: 78%
“…Results also open the question of the Q.Clear reconstruction optimization for each different radiopharmaceutical and clinical application. For example, it was recently reported that for 90 Y TOF PET imaging a β value of 4000 is the recommended choice, far more elevated than the values considered in the present work. This extreme case is due to the low statistics of 90 Y PET imaging, so different results than those presented in this study can be achieved for other nuclides or pharmaceuticals.…”
Section: Discussionmentioning
confidence: 78%
“…Finding an optimal β-value in clinical practice depends on finding a balance in counting statistics and resulting image quality. Others have suggested to use β-values of 400-500 for whole-body 18 F-FDG studies [14], 400 or 600 for pulmonary nodules evaluation [16,17], 350-400 for brain studies [18], 300 for 18 F-fluciclovine [19], and 4,000 for low-count 90 Y studies [20].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout our study we initially performed our analysis on all six reconstruction method variations. However, it became apparent to us that in combination with other's work [10,12] we could focus the presentation of data better as we advanced in this study by eliminating the presentation of results for methods that were inferior. Scott and McGowan concluded based on phantom studies that the optimal β value for the Q.Clear reconstruction method for Y 90 PET imaging was β = 1000 [10].…”
Section: Discussionmentioning
confidence: 91%
“…The most common post-TARE imaging protocol is 90 Y bremsstrahlung single-photon emission computed tomography (SPECT) to verify treatment deposition in the liver along with no extrahepatic microsphere deposition [1,12]. Due to the noisy nature of these images, they are typically used only for qualitative purposes because quantitative assessment is di cult [1,13].…”
Section: Introductionmentioning
confidence: 99%